Immune Thrombotic Thrombocytopenic Purpura Following Trimethoprim Sulfamethoxazole Reexposure: A Case Report - Renee Morecroft; Jyoti Moorjani; Mohamed Hussam Hallak; Tathana Rivera Hernandez; Isabella Estrada; Hammad Awad; Payam Nabizadeh‐Eraghi (Clinical Case Reports, 2026)
ABSTRACT An 85‐year‐old man developed acute neurologic dysfunction, severe thrombocytopenia, microangiopathic hemolytic anemia, and ADAMTS13 activity of 4.6% after TMP‐SMX reexposure. Seven plasma‐exchange sessions plus corticosteroids produced rapid recovery. This case highlights the diagnostic challenge of possible TMP‐SMX–associated iTTP and the importance of prompt treatment.